2021
DOI: 10.3390/antibiotics10020220
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Implementation of a Clinical Pharmacist-Driven Antimicrobial Stewardship Programme at a Tertiary Care Centre in South India

Abstract: In many parts of the world, including in India, pharmacist roles in antimicrobial stewardship (AMS) programmes remain unexplored. We describe the evolution and effect of the role of adding clinical pharmacists to a multidisciplinary AMS at a tertiary care teaching hospital in Kerala, India. Through effective leadership, multidisciplinary AMS (February 2016) and antitubercular therapy (ATT) stewardship programmes (June 2017) were established. Clinical pharmacists were introduced as core members of the programme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…In 23 studies, the common challenges faced by implementers and researchers were related to resources, including insufficient financial support for sustaining antimicrobial stewardship activities, shortage of human resources (such as microbiologists, pharmacists, and infectious disease specialists), and lack of technological support to facilitate the administration of interventions [ 38 , 42 46 , 48 – 50 , 58 , 62 , 63 , 67 , 69 – 71 , 73 , 75 77 , 79 , 85 , 86 ]. It was also commonly reported that prescribers participating in ASPs were often too busy to perform intervention activities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 23 studies, the common challenges faced by implementers and researchers were related to resources, including insufficient financial support for sustaining antimicrobial stewardship activities, shortage of human resources (such as microbiologists, pharmacists, and infectious disease specialists), and lack of technological support to facilitate the administration of interventions [ 38 , 42 46 , 48 – 50 , 58 , 62 , 63 , 67 , 69 – 71 , 73 , 75 77 , 79 , 85 , 86 ]. It was also commonly reported that prescribers participating in ASPs were often too busy to perform intervention activities.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, six studies reported that lack of motivation prevented behavior change of prescribers, as some were concerned about complaints from patients or reduction in salary if they refused to prescribe antibiotics [ 39 , 48 , 62 , 78 , 84 , 86 ].…”
Section: Resultsmentioning
confidence: 99%
“…Pharmacist-driven or pharmacist-led AMS programmes have been shown to improve antimicrobial prescriptions where there is a lack of availability of ID specialists. 26 , 27 However while it was recognized by the learners that involving pharmacists and nurses in AMS is beneficial, they believed the distinct roles remain ill-defined in many countries, creating a potential obstacle in the implementation of global AMR priorities. Even though theoretical advances from academia or policy describe nurses’ roles, these are yet to be translated to clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…This was reflected in the national guideline on AMS implementation originally issued in 2016 and updated in 2020 13 14. Sustained reductions have been achieved in antibiotic use by AMS teams across different settings including the example of non-specialist pharmacist-led programme in South Africa27 and clinician-led and clinical pharmacist-driven AMS programme in India 28. In our study, despite having no experience in clinical interactions, our junior pharmacists have been building their PAF capacity and gained promising results in the number of audits with feedback to the doctors.…”
Section: Discussionmentioning
confidence: 76%
“…13 14 Sustained reductions have been achieved in antibiotic use by AMS teams across different settings including the example of non-specialist pharmacist-led programme in South Africa 27 and clinician-led and clinical pharmacist-driven AMS programme in India. 28 In our study, despite having no experience in clinical interactions, our junior pharmacists have been building their PAF capacity and gained promising results in the number of audits with feedback to the doctors. Although the results were highly variable between hospitals, this shows the feasibility and potential of involving pharmacists in the prescription-based strategies for AMS programmes in LMICs.…”
Section: Discussionmentioning
confidence: 89%